Impact Of Organic Fertilizers and Microbial Inoculation on Soil Structure, Root Development and Maize Yield - Farhana; Muhammad Iqbal (Indus Journal of Bioscience Research, 2023)
Background: Zea mays L., commonly known as maize, is a crucial cereal crop for human consumption and is globally ranked third, following wheat and rice. Objectives: This study aimed to investigate the impact of organic fertilizers and microbial inoculation on soil structure, root development, and maize yield. Methods: A pot experiment was conducted at the Research Area of the Institute of Soil and Environmental Sciences, University of Agriculture Faisalabad, using a completely randomized design. Three levels of organic amendments (farmyard manure and fly ash) at 0, 5, and 10 Mg ha-1, combined with five different microbial inoculants, were applied. Hybrid maize (Shahenshah) was grown with recommended inorganic fertilizers. Soil physical parameters, plant growth parameters, and maize yield were measured and analyzed. Results: The results demonstrated that the combination of organic amendments and microbial inoculation significantly influenced the percentage of water-stable aggregates, indicating improved soil structure. Higher levels of organic matter addition led to increased CO2 emission, microbial activity, and decomposition, resulting in the formation of larger water-stable aggregates (>2.0 mm). The combined application of specific microbial inoculants and organic amendments enhanced microbial activity, promoting soil aggregate stability. Additionally, the study evaluated plant growth parameters, including plant and root fresh and dry weights, plant height, leaf area index (LAI), root length, and root length density (RLD). The combined application of organic fertilizers and microbial inoculants resulted in improved root development, increased plant biomass, and enhanced maize yield. Conclusion: Utilization of organic fertilizers and microbial inoculation had a significant positive impact on soil structure, root development, and maize yield. These findings emphasize the importance of incorporating organic amendments and beneficial microbes in agricultural practices to enhance soil quality and promote sustainable crop production.